Care When It Counts: Establishing Trauma-Sensitive Care as a Preventative Approach for 0-3-Year-Old Children Suffering from Trauma and Chronic Stress - Serafine Dierickx; Laura Malisse; Elisa Bisagno; Alessia Cadamuro; Sarah Van Haeken; Dorien Wuyts; Zane Linde-Ozola; Annija Kandãte; Dorottya Morva; Monika Rozsa; Andrea Gruber; Johanna M. C. Blom; et al. (MDPI AG, 2023)
Adverse childhood experiences are an important societal concern. Children aged 0-3 are particularly vulnerable to unpredictable chronic stress due to the critical period for brain development and attachment. Trauma-sensitive care is a preventative approach to reduce the burden of stressful experiences by committing to positive relationships. Professional caregivers are ideally placed to offer trauma-sensitive care; however, earlier research reveals that the tools they need to consciously apply trauma-sensitive care principles are missing. The current study organized living labs (co-creative research method) to present trauma-sensitive care as a preventative approach aimed at children aged 0-3. Two living labs were organized in Belgium and Hungary, where professional caregivers collaborated to create a protocol that offers guidelines on how to implement trauma-sensitive care. The resulting protocol included a theoretical foundation on trauma as well as a translation of these guidelines into practical recommendations. The protocol was evaluated by incorporating it into a training intervention delivered to 100 professional caregivers from childcare organizations across four European countries. The protocol received positive feedback from participants, with results indicating a self-reported increase in knowledge, attitude and practice of trauma-sensitive care principles. We conclude that this trauma-sensitive care protocol is a promising answer to the needs of professional caregivers working with children aged 0-3.